Basic ideas and concepts in nuclear physics: an introductory approach, Third edition - Heyde, Kris L. G. (Institute of Physics Pub., 2011)
The third edition of a classic book, Basic Ideas and Concepts in Nuclear Physics sets out in a clear and consistent manner the various elements of nuclear physics. Divided into four main parts: the constituents and characteristics of the nucleus; nuclear interactions, including the strong, weak and electromagnetic forces; an introduction to nuclear structure; and recent developments in nuclear structure research, the book delivers a balanced account of both theoretical and experimental nuclear physics.